Applications of Google Search Trends for risk communication in infectious disease management: A case study of the COVID-19 outbreak in Taiwan. (June 2020) - Husnayain, Atina; Fuad, Anis; Su, Emily Chia-Yu
Highlights: Searches related to COVID-19 and face masks in Taiwan increased rapidly following the announcements of Taiwan's first imported case and reached their peak as local cases were reported. Searches for handwashing were gradually increased in the period of face masks shortage in Taiwan. Google Trends provides information on the most common knowledge needed by users and location of searches. In response to the ongoing outbreak, our results demonstrated that Google Trends could potentially define the proper timing and location for practicing appropriate risk communication strategies to the affected population. Abstract: Objective: An emerging outbreak of a novel coronavirus, COVID-19, has now been detected in at least 211 countries worldwide. Given this pandemic situation, robust risk communication is urgently needed, particularly in affected countries. Therefore, this study explored the potential use of Google Trends (GT) to monitor public restlessness toward COVID-19 infection in Taiwan. Methods: We retrieved GT data for the specific locations and subregions in Taiwan nationwide using defined search terms related to the coronavirus, handwashing, and face masks. Results: Searches related to COVID-19 and face masks in Taiwan rapidly increased following the announcements of Taiwan's first imported case and reached a peak as locally acquired cases were reported. However, searches for handwashing gradually increased during the period of face-mask shortage. Moreover, high to moderate correlations between Google relative search volumes (RSVs) and COVID-19 cases were found in Taipei (lag-3), New Taipei (lag-2), Taoyuan (lag-2), Tainan (lag-1), Taichung (lag0), and Kaohsiung (lag0). Conclusion: In response to the ongoing outbreak, our results demonstrated that GT could potentially define the proper timing and location for practicing appropriate risk communication strategies for affected populations.